Methodical principles of teaching Ancient Armenian language in textbooks of M. Abeghyan - Dilbaryan, Narine (Bulletin of Yerevan University B: Philology, 2024)
In the history of Armenian linguistics, Manuk Abeghyan is known primarily for his theoretical innovative monographs and textbooks devoted to the study and teaching of the grammar of the modern Armenian language, but in this article we prove that his works and textbooks of the Ancient Armenian language are just as valuable, and most importantly, as innovative, like all his philological heritage. Manuk Abeghyan was a talented linguist and researcher and and at the same time he was a great educator, teacher, for whom it was extremely important to teach children and the younger generation the Armenian literary language in all its forms - ancient Armenian, modern Armenian and its dialects, so that the new generation could read and understand ancient manuscripts, translate them. In textbooks of the ancient Armenian language, M. Abeghyan has always been a supporter of new principles of teaching. He was the first to begin teaching the ancient Armenian language with lessons on conjugating verbs, emphasizing the fact that the verb has a main function in the process of speech formation; if the student knows how to conjugate a verb, knows its moods, tenses, aspects, then he will be able to form correct speech and correctly translate different texts.